Supply chain reengineering in a paint company using axiomatic design - VAYVAY, ÖZALP (SPRINGER LONDON LTD, 2011)
The purpose of this paper is to outline the importance and benefits an organization can achieve through using a decomposition-based decision-making tool incorporating supply chain-balanced scorecard performance measures for supply chain reengineering. An axiomatic design-based model built on the insights gained from supply chain performance measures and reengineering model is applied to a paint company. The model aids supply chain reengineering by identifying the scope of the reengineering design. The resultant reengineering design based on the needs and strategies of the firm in question is presented. A thorough simulation study follows to impart substantial improvements. The case displays how the model can help companies adopt a more structured approach to the complicated problem of supply chain reengineering. This paper focuses on supply chain reengineering models where no conclusive work exists and is expected to fill a gap in the area and be instrumental to both researchers and practitioners by providing a direction for coherent decision making on supply chain reengineering studies.
Keywords: Supply chain management; Reengineering; Performance measurement; Axiomatic design; Case study; MANUFACTURING SYSTEM-DESIGN; MANAGEMENT; INTEGRATION; REDESIGN